2014
DOI: 10.3171/2013.8.jns13535
|View full text |Cite
|
Sign up to set email alerts
|

True petroclival meningiomas: results of surgical management

Abstract: Object The relentless natural progression of petroclival meningiomas mandates their treatment. The management of these tumors, however, is challenging. Among the issues debated are goals of treatment, outcomes, and quality of life, appropriate extent of surgical removal, the role of skull base approaches, and the efficacy of combined decompressive surgery and radiosurgery. The authors report on the outcome in a series of patients treated with the goal of total removal. Methods The authors conducted a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
126
1
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 42 publications
5
126
1
16
Order By: Relevance
“…Of the three subtype of PCMs mentioned above, those with the clivus type achieved GTR at the rate of 92.9 % (26 cases in 28 patients); 61.5 % (8 cases in 13 patients) of those with the petroclival type achieved GTR; on the other hand, 52.2 % (12 cases in 23 patients) of the petroclivosphenoidal type achieved and GTR (Table 3). And encouragingly the rate of GTR of our group was not lower or even higher than other approaches [10,[24][25][26]. We found that most of the patients recovered significantly and satisfactorily.…”
Section: Discussionsupporting
confidence: 51%
“…Of the three subtype of PCMs mentioned above, those with the clivus type achieved GTR at the rate of 92.9 % (26 cases in 28 patients); 61.5 % (8 cases in 13 patients) of those with the petroclival type achieved GTR; on the other hand, 52.2 % (12 cases in 23 patients) of the petroclivosphenoidal type achieved and GTR (Table 3). And encouragingly the rate of GTR of our group was not lower or even higher than other approaches [10,[24][25][26]. We found that most of the patients recovered significantly and satisfactorily.…”
Section: Discussionsupporting
confidence: 51%
“…Una muestra de 271 pacientes, luego del análisis multivariado encontraron que no existen diferencias significativas en cuanto a la recurrencia según localización [17], en estas localizaciones los meningiomas envuelven estructuras neurovasculares relevantes, lo que ratifica que es mejor preservar la función, que lograr resecciones completas con discapacidades permanentes [20]. Estos estudios contrastan con los obtenidos por Al-Mefty que logra resecciones Simpson de los pacientes con lesiones petroclivales [21], lo que reafirma la importancia de la experiencia quirúrgica.…”
Section: Discusionunclassified
“…Si bien la limitación de este estudio y práctica es el tamaño de la muestra, se lograron estándares internacionales en cuanto a los grados de resección y se aplicaron las técnicas microscópicas descritas para lograr el mayor beneficio [17,[20][21].…”
Section: Discusionunclassified
“…Permanent surgical morbidity remained in 20 % of patients during the average long-term follow-up of almost 10 years, but significantly more patients lived independently after than before surgery (61 vs 46 %). One-fourth of patients were lost to longterm follow-up, so that the numbers regarding long-term outcome must be appreciated with sound judgment.These key data focusing on medium and large petroclival meningioma are important, although difficult to compare with the smaller unselected series [1,3,[7][8][9]12]. Petroclival meningiomas smaller than 2 cm carry a much smaller surgical risk than large tumours, and in unselected series the small tumours dilute information regarding the problematic larger tumours.…”
mentioning
confidence: 99%
“…These key data focusing on medium and large petroclival meningioma are important, although difficult to compare with the smaller unselected series [1,3,[7][8][9]12]. Petroclival meningiomas smaller than 2 cm carry a much smaller surgical risk than large tumours, and in unselected series the small tumours dilute information regarding the problematic larger tumours.…”
mentioning
confidence: 99%